Pendekatan Matriks Ketetanggaan Berbobot untuk Solusi Minimum Spanning Tree (MST) - Tri Yani Akhirina; Thomas Afrizal (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
Minimum Spanning Tree (MST) or often called Minimum Weighting Spanning Tree (MWST) is a path or edge search algorithm that connects all vertices in a connected graph and does not form a circuit with a minimum weight. The classic algorithm used to solve MST problems is the Prim’s and Kruskal’s algorithms. The problem of minimum spanning tree is a problem related to optimization in finding the minimum weighted edge that can connect all vertices). MST is widely used in computer science such as to determine access points, build networks and many more. The purpose of this reserarch is to find new solutions that can provide alternative MST solutions besides classical algorithms such as Prim and Kruskal. This experimental research uses a weighted adjacency matrix approach,  with weight taken from the minimum side in each pair of matrix to produce a minimum spanning tree. This new solution can be an alternative in solving the minimum spanning tree problems.